2003
DOI: 10.1046/j.1460-9568.2003.02627.x
|View full text |Cite
|
Sign up to set email alerts
|

A subpopulation of rats show social and sleep–waking changes typical of chronic neuropathic pain following peripheral nerve injury

Abstract: Neuropathic conditions for which treatment is sought, the so-called chronic pain syndrome, are characterized usually by complex behavioural disturbances as well as pain. In this study we evaluated whether social behavioural and sleep disruptions occurred after nerve injury. Before and after chronic constriction of the sciatic nerve, resident-intruder and sleep-wake cycles, as well as mechanical and thermal allodynia/hyperalgesia, were quantified. Sciatic nerve injury in all animals reduced withdrawal threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
113
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 79 publications
18
113
1
1
Order By: Relevance
“…Although the number of ultrasonic vocalizations emitted by neuropathic rats does not appear to differ from control animals, it should be noted that a similar negative correlation was reported for polyarthritic animals in this study by Jourdan and colleagues [39], in contrast to other reports [38]. Similarly, the first study to measure either sleep or EEG patterns in rats with a chronic constriction injury failed to show any changes in these parameters for up to 146 days after surgery [40], However, more recent studies report contrasting observations [41,42] in which CCI rats have altered sleep patterns. Furthermore, Monassi et al have shown that only CCI rats that exhibit either transient or enduring changes in dominant behaviour in response to an intruder (which is characteristic of impaired social functioning) exhibit sleep disturbance [42].…”
Section: Spontaneous Painsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the number of ultrasonic vocalizations emitted by neuropathic rats does not appear to differ from control animals, it should be noted that a similar negative correlation was reported for polyarthritic animals in this study by Jourdan and colleagues [39], in contrast to other reports [38]. Similarly, the first study to measure either sleep or EEG patterns in rats with a chronic constriction injury failed to show any changes in these parameters for up to 146 days after surgery [40], However, more recent studies report contrasting observations [41,42] in which CCI rats have altered sleep patterns. Furthermore, Monassi et al have shown that only CCI rats that exhibit either transient or enduring changes in dominant behaviour in response to an intruder (which is characteristic of impaired social functioning) exhibit sleep disturbance [42].…”
Section: Spontaneous Painsupporting
confidence: 81%
“…Similarly, the first study to measure either sleep or EEG patterns in rats with a chronic constriction injury failed to show any changes in these parameters for up to 146 days after surgery [40], However, more recent studies report contrasting observations [41,42] in which CCI rats have altered sleep patterns. Furthermore, Monassi et al have shown that only CCI rats that exhibit either transient or enduring changes in dominant behaviour in response to an intruder (which is characteristic of impaired social functioning) exhibit sleep disturbance [42].…”
Section: Spontaneous Painmentioning
confidence: 99%
“…Finally, it also was suggested that changes in serotonin content might also account for diurnal pain sensitivity as frontal pole, but not hippocampal or amygdala, serotonin levels correlated with pain thresholds (Schlosberg and Harvey, 1978). To our knowledge, no preclinical study has demonstrated diurnal variations in pain thresholds in an animal model of neuropathic pain, although sleep disturbances thought to be a more valid measure of pain intensity have been reported compared control animals (Monassi et al, 2003). In human studies, Petraglia et al (1983) found a circadian rhythm to beta-endorphin concentrations which peaked at 08:00 h and were lowest at 20:00 h. Hindmarsh et al (1989) reported that beta-endorphin levels were significantly higher in the morning compared to the afternoon in both human adults and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Following CCI, rats exhibit abnormal posture of the injured hindpaw (toes held together and plantar-flexed and paw everted), as well as repeated shaking, guarding and licking of the injured hindpaw suggesting the presence of spontaneous pain 9 . In addition to sensory dysfunction, several investigators have shown that CCI evokes behavioural disabilities, such as disrupted social interactions, sleep disturbances, depressive-like and anxiety-like behaviours [10][11][12][13] , however this is in contrast to the failure to find such behavioural disabilities by others 14,15 . CCI is therefore commonly used to investigate both the pathophysiology, and potential therapeutic agents for treatment of neuropathic pain.…”
mentioning
confidence: 99%